On Rainbow Vertex Antimagic Coloring of Graphs: A New Notion - Marsidi, Marsidi; Agustin, Ika Hesti; Dafik, Dafik; Kurniawati, Elsa Yuli (Mathematics Department, Maulana Malik Ibrahim State Islamic University of Malang, 2021)
All graph in this paper are simple, finite, and connected. Let be a labeling of a graph . The function is called antimagic rainbow edge labeling if for any two vertices and , all internal vertices in path have different weight, where the weight of vertex is the sum of its incident edges label. The vertex weight denoted by for every . If G has a antimagic rainbow edge labeling, then is a antimagic rainbow vertex connection, where the every vertex is assigned with the color . The antimagic rainbow vertex connection number of , denoted by , is the minimum colors taken over all rainbow vertex connection induced by antimagic rainbow edge labeling of . In this paper, we determined the exact value of the antimagic rainbow vertex connection number of path ( ), wheel ( ), friendship ( ), and fan ( ).